Testing of subjective perception of complexity of signs of Czech sign language - Langer, Jiří; Rypka, Miroslav (Journal of Exceptional People, 2017)
The contribution focuses on expanding the theoretical basis for teaching the Czech sign language (hereinafter CSL) and for its particular grammatical description. This knowledge is a necessary condition for efficient teaching both of deaf users (prelingually deaf children) and of hearing users (parents and family members, students of special pedagogy, interpreters etc.). More concretely, it reports on the results of research focusing on the subjective assessment of the perception of complexity of signs of CSL from the perspective of potentially hearing students. Another aim of the study was verification of the designed theoretical concept of counting of the number of morphemes in the CSL signs whose number is one of the crucial variables during the process of hierarchical dependences and subsequent verification of the validity of Menzerath-Altmann law in the case of CSL. In total, 28 signs of CSL were tested while those belong into 7 groups of motion matrices, while 235 respondents subjectively expressed via five-degree Likert scale their opinion on the complexity of a particular sign. From the results, it is concluded that there exists a direct proportional linear dependence between the number of morphemes of individual signs and assessment of their complexity. Based on the discovered results, also an adjustment of the way how to count morphemes was designed for the needs of further qualitatively linguistic analysis.
Keywords: posunková komunikace; lingvistika; Persons with Hearing Disabilities; Česká republika; lidé; Sign Language; Adult; Czech Republic; sluchově postižení; dospělí; Linguistics; Education of Persons with Hearing Disabilities; Manual Communication; výuka sluchově postižených; Humans; znaková řeč